Hitchhiking motility of Staphylococcus aureus involves the interaction between its wall teichoic acids and lipopolysaccharide of Pseudomonas aeruginosa - Liu, Chao-Chin; Lin, Mei-Hui (Frontiers in Microbiology, 2023)
Staphylococcus aureus, which lacks pili and flagella, is nonmotile. However, it hitchhikes motile bacteria, such as Pseudomonas aeruginosa, to migrate in the environment. This study demonstrated that the hitchhiking motility of S. aureus SA113 was reduced after the tagO, which encodes an enzyme for wall teichoic acids (WTA) synthesis, was deleted. The hitchhiking motility was restored after the mutation was complemented by transforming a plasmid expressing TagO into the mutant. We also showed that adding purified lipopolysaccharide (LPS) to a culture that contains S. aureus SA113 and P. aeruginosa PAO1, reduced the movement of S. aureus, showing that WTA and LPS are involved in the hitchhiking motility of S. aureus. This study also found that P. aeruginosa promoted the movement of S. aureus in the digestive tract of Caenorhabditis elegans and in mice. In conclusion, this study reveals how S. aureus hitchhikes P. aeruginosa for translocation in an ecosystem. The results from this study improve our understanding on how a nonmotile pathogen moves in the environment and spreads in animals.